Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.2478/s11536-009-0121-7
|View full text |Cite
|
Sign up to set email alerts
|

Herbal remedies are the main etiologic factor in melanosis coli, a case series study

Abstract: AbstractMelanosis coli is a brown to black discoloration of the colon mucosa usually associated with long-term ingestion of laxatives. However, melanosis coli can be found in patients with no history of laxative use. Regular use of herbal remedies could be the major source of anthranoid laxatives in such patients. We designed a prospective case series study to identify the clinical characteristics and etiology of melanosis coli in affected patients. This study took place in Ank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…3 , 7 , 8 But predominant descending colon and rectum involvement as well as diffuse whole-length colonic involvements, were also reported. 4 , 14 Our patient is also found to have diffuse colonic involvement.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…3 , 7 , 8 But predominant descending colon and rectum involvement as well as diffuse whole-length colonic involvements, were also reported. 4 , 14 Our patient is also found to have diffuse colonic involvement.…”
Section: Discussionsupporting
confidence: 54%
“…9 Herbal teas containing senna, which are commonly ingested by individuals for their laxative and weight loss effect, are reported to have associations with the development of Melanosis coli . 4 California herbal tea, which is used by our patient, is one of those teas containing senna. 10…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some traditional natural medicines, such as rhubarb, senna leaves, and aloe, used to treat constipation contain diarrheal ingredients. Clinical practice has confirmed that the long-term use of rhubarb, senna leaves, and aloe may result in colorectal melanosis, which may induce colorectal cancer development ( Kav and Bayraktar, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Its genotoxicity and DNA-damaging properties also have been found by in-vitro study (Li et al, 2010). Furthermore, many case reports (Han et al, 2010; Kav and Bayraktar, 2010) have shown that chronic use of anthranoid laxatives and weight-loss products may cause melanosis coli (MC), which can increase the risk of colonic neoplasm (van Gorkom et al, 1999). This suggests that the safety of long-term use of emodin should be carefully considered, in agreement with the conclusion from previous studies (Dong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%